Effects of Three Fertilizers on Improving Soil Characteristics and Growth Performance of Mahonia fortunei (Lindl.) Fedde in Rocky Desertification Areas - Xiuwen Fang; Yue Sun; Xiangxiang Huang; Bo Pan; Haiying Gao; Zhishui Liang (Land)
Rocky desertification, a severe form of land degradation in tropical and subtropical regions driven by vegetation loss and soil erosion, poses significant ecological and economic challenges. Field trials in Fengshan County, Guangxi, China, evaluated the efficacy of NPK compound fertilizers, slow-release fertilizers, and bio-organic fertilizers on soil rehabilitation, microbial diversity, and the growth of Mahonia fortunei, a key species for ecological restoration and understory cash crop cultivation. The results demonstrated the bio-organic fertilizer’s superiority in soil regeneration, increasing organic matter by 30.4% (Bolin), 15.73% (Longlai), and 21.83% (Longlei) compared to NPK compound fertilizers, alongside elevating the total nitrogen (reaching 19.4 g/kg in Bolin) and phosphorus (85.45% higher in Bolin). Bio-organic fertilizer increased enzyme activities by 27–202% and enhanced microbial diversity, notably Proteobacteria and Actinobacteria. Slow-release fertilizers maximized micronutrient availability (e.g., Cu increased by 151.65% in Bolin) and improved plant growth, achieving peak Mahonia fortunei (Lindl.) Fedde height (3.62 cm, increasing 9.04%) and ground diameter (4.5 cm, increasing 18.42%) in Longlei compared to NPK compound fertilizers. Regional variability highlighted the bio-organic fertilizer’s dominance in soil fertility metrics, while slow-release formulations excelled in micronutrient enrichment and plant performance. NPK compound fertilizers exhibited the lowest efficacy, potentially exacerbating soil degradation. This study advocates integrating bio-organic fertilizers for soil regeneration with targeted slow-release applications for crop productivity, particularly in understory cash crop systems. Such a dual approach bridges ecological restoration with economic resilience in karst ecosystems, offering scalable solutions for global rocky desertification mitigation.